2022
DOI: 10.1001/jamapediatrics.2021.5563
|View full text |Cite
|
Sign up to set email alerts
|

Association of Birth During the COVID-19 Pandemic With Neurodevelopmental Status at 6 Months in Infants With and Without In Utero Exposure to Maternal SARS-CoV-2 Infection

Abstract: IMPORTANCEAssociations between in utero exposure to maternal SARS-CoV-2 infection and neurodevelopment are speculated, but currently unknown.OBJECTIVE To examine the associations between maternal SARS-CoV-2 infection during pregnancy, being born during the COVID-19 pandemic regardless of maternal SARS-CoV-2 status, and neurodevelopment at age 6 months. DESIGN, SETTING, AND PARTICIPANTSA cohort of infants exposed to maternal SARS-CoV-2 infection during pregnancy and unexposed controls was enrolled in the COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
167
2
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(201 citation statements)
references
References 72 publications
7
167
2
5
Order By: Relevance
“…Early signals of adverse neurodevelopmental outcomes at 3-6 months, 1 year, and 1.5 years in infants and children exposed to SARS-CoV-2 in utero, and/or born during the COVID-19 pandemic are emerging [37][38][39][40][41]. A longitudinal cohort study of 57 infants with prenatal exposure to SARS-CoV-2 in China identified deficits in the social-emotional domain of neurodevelopmental testing at 3 months of age [40].…”
Section: Early Evidence Of Adverse Neurodevelopmental Outcomes In Chi...mentioning
confidence: 99%
“…Early signals of adverse neurodevelopmental outcomes at 3-6 months, 1 year, and 1.5 years in infants and children exposed to SARS-CoV-2 in utero, and/or born during the COVID-19 pandemic are emerging [37][38][39][40][41]. A longitudinal cohort study of 57 infants with prenatal exposure to SARS-CoV-2 in China identified deficits in the social-emotional domain of neurodevelopmental testing at 3 months of age [40].…”
Section: Early Evidence Of Adverse Neurodevelopmental Outcomes In Chi...mentioning
confidence: 99%
“…A recent, larger study compared 114 infants exposed to SARS‐CoV‐2 in utero with 141 infants not exposed to SARS‐CoV‐2 but also born during the pandemic. 103 There were no differences on the Ages and Stages Questionnaire, Third Edition at 6 months of age as a function of infection status, timing during gestation, or severity of maternal illness. However, when these groups were compared with historical controls born before the pandemic, both groups born during the pandemic had significantly decreased gross motor, fine motor, and personal‐social Ages and Stages Questionnaire, Third Edition scores.…”
Section: Role Of the Brain Developmental Stagementioning
confidence: 83%
“…There has been little previous work in this area to date [42]. A study has shown that in utero exposure to maternal SARS-CoV-2 infection is not associated with neurodevelopmental outcome at age 6 months [11], and another study has shown that newborns exposed in utero to SARS-CoV-2 have largely normal neurological development in the first few months of life. There is an ongoing multicenter observational study currently recruiting that also aims to review neurodevelopmental outcomes at six months [43], although longer-term follow-up is required to provide a more accurate picture.…”
Section: Discussionmentioning
confidence: 99%
“…Although most neonates with SARS-CoV-2 infections have mild disease, the impact on long-term neurodevelopmental outcomes is currently unknown. It has been shown that birth during the COVID-19 pandemic, but not in utero exposure to maternal SARS-CoV-2 infection, is associated with neurodevelopmental outcome differences at age 6 months [11]. Another study has shown that newborns exposed in utero to SARS-CoV-2 have largely normal neurological development in the first few months of life [12].…”
Section: Introductionmentioning
confidence: 99%